WHO Expert Committee on Rabies : seventh report, meeting held in Geneva from 20 to 27 September 1983 - World Health Organization; World Health Organization (WHO) (Geneva : World Health Organization, 1984)
An expert review of world knowledge on rabies, in human and animal populations, and the methods available for its control. Sections review recent advances in laboratory diagnosis, human and animal vaccines, testing, prevention, treatment, and national programmes for control, particularly concerning the problem of rabies in dogs and other domestic pets. Highlights include the application of monoclonal antibody studies of the virus, the use of cell culture technology to create better vaccines, and the successful introduction of oral vaccines for the immunization of foxes and other wildlife. The involvement of vampires and other bats in epidemics is also reviewed. The book concludes with a detailed guide to post-exposure treatment in man, strongly recommending the combined administration of antirabies serum and vaccine, together with local treatment of the wound, as the best possible prophylaxis of rabies in an exposed person. Dose schedules for several types of vaccine and antisera are given, together with advice on the intensive-care treatment of clinical rabies in man and the precautions needed to protect hospital personnel.
Keywords: WHO Expert Committee on Rabies